Control of the strain field near the crack in elastic layer - Ciarletta, M.; Iovane, G.; Sumbatyan, M. A. (Нелінійні коливання, 2005)
In the present paper we consider the strain analysis near the crack parallel to boundary surfaces of a linear isotropic elastic layer of constant thickness. We pose the problem to minimize opening of the crack’s faces, when a normal force is applied to a boundary of the layer. The control secondary loading is a normal stress uniformly distributed over the boundary surfaces as to oppose the opening caused by the external applied force. We show that the most dangerous are tangential deformations, and the normal ones are always by many times less dangerous Проаналiзовано пружнiсть бiля трiщини, яка паралельна межi поверхнi лiнiйного iзотропного пружного шару сталої товщини. Ставиться проблема мiнiмiзацiї ширини трiщини у випадку, коли на межi шару дiє нормальна сила. Вторинним керуючим навантаженням є нормальне напруження, рiвномiрно розподiлене по межi поверхонь, яке протидiє розширенню трiщини, що виникає пiд дiєю зовнiшньо прикладеної сили. Показано, що найбiльш загрозливими є тангенцiальнi деформацiї, а нормальнi деформацiї завжди в багато разiв менш загрозливi.